A preliminary study of course information on i-Learn perspective: focusing on accessibility, contents and user interface parameters / Mohd Nor Hajar Hasrol Jono . .. [et al.] - Hasrol Jono, Mohd Nor Hajar; Abdul Aziz, Azlan; Mat Zain, Nurul Hidayah; Endut, Nor Adora; Abdul Aziz, Siti Rahayu; Ramakrisnan, Prasanna (Penerbit UiTM (UiTM Press), 2009)
i-Learn serves as UiTM’s Learning Management System (LMS) portal; launched by the i-Learn Center (iLeC) in its aim to provide strategic adaptation of e-learning at the university. The portal includes, as one of its contents, the Course Information module useful as a guideline for lecturers as well as students to understand the structure and content of the courses or subjects being offered. This study aims at analyzing the characteristic effectiveness of the i-Learn portal particularly the Course Information Module focusing on aspects of accessibility, content and user interface parameters. The analysis was based on the results of questionnaires, taking UiTM’s lecturers as the respondents. We measured whether the course information tool is useful in terms of speed and ease of use based on the Technology Acceptance Model (TAM). Finally, we present a brief discussion concerning the obtained results as well as future plans for utilizing the findings of this study.